2004
DOI: 10.1128/mcb.24.15.6690-6700.2004
|View full text |Cite
|
Sign up to set email alerts
|

Rap1 Regulates the Formation of E-Cadherin-Based Cell-Cell Contacts

Abstract: In epithelial tissues, cells are linked to their neighbors through specialized cell-cell adhesion proteins. E-cadherin is one of the most important membrane proteins for the establishment of intimate cell-cell contacts, but the molecular mechanism by which it is recruited to contact sites is largely unknown. We report here that the cytoplasmic domain of E-cadherin interacts with C3G, a guanine nucleotide exchange factor for Rap1. In epithelial cell cultures, ligation of the extracellular domain of E-cadherin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
246
1
5

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 240 publications
(262 citation statements)
references
References 40 publications
10
246
1
5
Order By: Relevance
“…In contrast to the observation in MCF7 cells that junction disassembly is not initiated by RapGAP expression, this causes junction disassembly, including loss of the tight junction protein ZO-1 in endothelial cells (Hogan et al, 2004;Wittchen et al, 2005). In spite of this, Rap1-induced regulation of E-cadherin and VEcadherin may not be a general mechanism for all classical cadherins since overexpression of RapGAP in HEK293 cells does not affect N-cadherin-mediated cell-cell junction formation (Hogan et al, 2004).…”
Section: Rap1 and The Regulation Of Ve-cadherinmentioning
confidence: 75%
See 3 more Smart Citations
“…In contrast to the observation in MCF7 cells that junction disassembly is not initiated by RapGAP expression, this causes junction disassembly, including loss of the tight junction protein ZO-1 in endothelial cells (Hogan et al, 2004;Wittchen et al, 2005). In spite of this, Rap1-induced regulation of E-cadherin and VEcadherin may not be a general mechanism for all classical cadherins since overexpression of RapGAP in HEK293 cells does not affect N-cadherin-mediated cell-cell junction formation (Hogan et al, 2004).…”
Section: Rap1 and The Regulation Of Ve-cadherinmentioning
confidence: 75%
“…Furthermore, adhesion of ovarian carcinoma cells (OVCAR) to Fc-E-cadherin is inhibited by expression of dominant negative Rap1, which means that Rap1 regulates E-cadherin directly (Price et al, 2004). Importantly, Hogan et al found that the introduction of RapGAP into MCF7 cells does not disrupt mature E-cadherin-based cell-cell junctions but strongly reduces the reformation of adherens junctions upon re-addition of Ca 2+ (so-called Ca 2+ switch), which supports the idea that Rap1 has a role in junction maturation, not maintenance (Hogan et al, 2004). Remarkably, the tight junction marker ZO-1 is present at cell-cell contacts after Ca 2+ chelation.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…RAP1A belongs to the family of Ras-like GTPases, whose function is in enhancing cell-matrix and cell-cell adhesion in an integrin-dependent manner, and enhancing cell-cell contact formation through E-cadherins (Hogan et al, 2004). Another integrin-dependent molecule, ILK (integrin-linked kinase), is a serine-threonine protein kinase that can interact directly with b-integrin.…”
Section: Discussionmentioning
confidence: 99%